ChemInform Abstract: Synthesis, Structural and Optical Characterization of APbX3 (A: Methylammonium, Dimethylammonium, Trimethylammonium; X: I, Br, Cl) Hybrid Organic‐Inorganic Materials. Issue 34 (4th August 2016) - Mancini, Alessandro; Quadrelli, Paolo; Amoroso, Giuseppe; Milanese, Chiara; Boiocchi, Massimo; Sironi, Angelo; Patrini, Maddalena; Guizzetti, Giorgio; Malavasi, Lorenzo
Abstract: APbX3 (A: MeNH3 +, Me2 NH2 +, Me3 NH + ; X: I, Br) hybrid organic‐inorganic compounds are prepared by dissolving appropriate amounts of Pb(O‐Ac)2 in excess HX (100 °C) followed by the addition of the respective amine (25—40% in H2 O) in stoichiometric quantities and subsequent cooling to 46 °C at a rate of 1 °C/min.